Greek epigraphy and religion: papers in memory of Sara B. Aleshire from the Second North American Congress of Greek and Latin Epigraphy - Mackil, Emily Maureen; Papazarkadas, Nikolaos; Aleshire, Sara B. (Brill studies in Greek and Roman epigraphy, 2021)
"The second North American Congress of Greek and Latin Epigraphy was held January 4-6, 2016 on the campus of the University of California, Berkeley [...]. It was due to both the overall number of papers and the special concentration of papers on Greek epigraphy and religion that we, the organizers, chose to publish the proceedings in two volumes. The first, more general volume, From Document to History: Epigraphic Insights into the Greco-Roman World, edited by Carlos Noreña and Nikolaos Papazarkadas, is now joined by this publication [...]." (Preface)